The Effectiveness of Mindfulness-Based Cognitive Therapy on Anxiety, Happiness and Mindfulness in Nurses - Maryam Talebi (Hamadan University of Medical Sciences, 2021)
Introduction: Psychological health is recognized as an important source of adaptation to workplace problems. The aim of this study was to evaluate the effectiveness of mindfulness-based cognitive therapy on the level of anxiety, happiness and mindfulness in nurses. Methods: The research method was experimental with pre- and post-test design with control group. For this purpose, 60 nurses of Babol city, Iran, in 2019 were randomly assigned to two experimental groups (30) and control (30). Mindfulness, Attention, and Awareness Scale (MAAS), Happiness Libomirsky (SHS), and Spielberger (STAAI-X) were performed before and after treatment. Participants in the experimental group were trained in groups for 8 sessions of 90 minutes. Multivariate analysis of covariance was used to analyze the data. Results: The mean of mindfulness and happiness for both groups increased in the post-test phase, which is higher in the experimental group; also, the results of analysis of covariance for anxiety showed that meditation has no significant effect on anxiety but has significantly increased happiness in the experimental group. Conclusion: The results of the present study showed that cognitive therapy based on mindfulness has increased awareness in the behavioral characteristics of the experimental group in the post-test stage. It seems that cognitive therapy based on mindfulness has a positive effect on increasing happiness and mindfulness in nurses.